Implication of RAGE Polymorphic Variants in COPD Complication and Anti-COPD Therapeutic Potential of sRAGE. (2nd November 2021) - Malik, Parth; Hoidal, John R.; Mukherjee, Tapan Kumar
Abstract: Chronic obstructive pulmonary disease (COPD) is a slowly progressive and poorly reversible airway obstruction disease. It is caused either alone or in combination of emphysema, chronic bronchitis (CB), and small airways disease. COPD is thought to be a multi-factorial disorder in which genetic susceptibility, environmental factors and tobacco exposure could be doubly or simultaneously implicated. Available medicines against COPD include anti-inflammatory drugs, such as β2-agonists and anticholinergics, which efficiently reduce airflow limitation but are unable to avert disease progression and mortality. Advanced glycation end products (AGE) and their receptors i.e. receptor for advanced glycation end products (RAGE) are some molecules that have been implicated in the complication of COPD. Several RAGE single nucleotide polymorphic (SNP) variants are produced by the mammalian cells. Based on the ethnicity some SNPs aggravate the COPD severity. Mammalian cells produce several alternative RAGE splice variants including a soluble RAGE (sRAGE) and an endogenous soluble RAGE (esRAGE). Both of these act as decoy receptor and thus may help to arrest the COPD complications. Several lines of evidences indicate a decreased level of sRAGE in the COPD subjects. One of the new strategies to reduce COPD complication may be sRAGE therapeutic administration to the COPD subjects. This comprehensive discussion sheds light on the role of RAGE and its polymorphic variants in the COPD complication along with sRAGE therapeutic significance in the COPD prevention.